PECULIARITIES OF THE III TYPE INTERFERON GENES’ POLYMORPHISM IN HCV PATIENTS ON THE CROSS-BORDER REGIONS OF RUSSIA AND MONGOLIA - I. V. Malov; O. Baatarkhuu; O. B. Ogarkov; L. A. Stepanenko; P. Nyamdawa; J. Oyunbileg; S. I. Malov; E. D. Savilov; J. Amarsanaa; D. Gantulga (Журнал инфектологии, 2017)
Aims: determine the structure of IFNL3/IFNL4 interferon genes’ polymorphism in healthy people and in HCV patients and the frequency of spontaneous viral clearance in ethnic groups of Caucasians and Mongolians, living in the Asian part of Russia (Irkutsk Region) and in Mongolia. Materials and methods: population genetic studies were conducted at 669 patients with hepatitis C, including 567 representatives Caucasian and 102 Mongoloid races. The control group consisted of 1520 healthy individuals, blood donors (800 Caucasians and 720 Mongoloids). Results: it was found that in Caucasians patients with chronic hepatitis C were significantly less common CC genotype rs12979860, TT genotype rs8099917 and TT/TT genotype rs368234815, than in the general population. However, in patients with chronic hepatitis C, the representatives of the Mongoloid race, compared with healthy individuals, significant differences were found only in relation to the TT genotype rs8099917 IFNL3 gene. Spontaneous clearance of the virus was significantly more common in the Mongoloid race than in Caucasians. Conclusions: the spontaneous viral clearance after clinical evidence or latent suffering hepatitis C was significantly more common in the Mongoloid race than in Caucasians that genetically determined high rate of prevalence in the population of the Mongols CC genotype rs12979860, TT genotype rs8099917 and TT/TT genotype rs368234815 polymorphisms of interferon type III genes.